Wilms Tumor - van den Heuvel-Eibrink (Exon Publications, 2016)
Wilms tumor is a rare kidney cancer that is usually diagnosed in children under the age of six. Wilms tumor is mostly the result of aberrations in WT1 gene, located on chromosome 11p13. In addition to being a risk factor for Wilms tumor, WT1 aberrations cause extra renal complications and other malignancies. This book brings together the basic and clinical aspects of Wilms tumor and WT1 research under three sections. Section I provides a comprehensive guide to the epidemiology, diagnostics, management, and treatment of Wilms tumor. Section II covers the biological aspects of Wilms tumor and WT1. Section III focuses on the role of WT1 in cardiac development, prostate cancer, glioblastoma and minimal residual disease.